Suitable nanoporous materials and refrigerants for a force-induced heat pump applicable to mesoporous materials - Ryosuke Shinozuka; Kazuya Kanamaru; Shinichiroh Iwamura; Masashi Ito; Masanobu Uchimura; Ami Ikura; Yasushi Ichikawa; Kazuki Sone; Hirotomo Nishihara (Energy Materials and Devices)
Although a new-class of heat pumps based on mechanically flexible nanoporous materials holds great potential for the utilization of sustainable refrigerants with a considerably high coefficient of performance (COP), reducing their system volume remains a challenge. In this study, we explored the potential of this innovative type of heat pump in terms of COP and system volume. To broaden the scope of material exploration, we devised a new thermodynamic heat pump system applicable to soft mesoporous materials, in addition to the conventional system that is suitable only for flexible microporous materials. Several key factors have been identified through the comparison of various nanoporous materials and refrigerants. Our systematic investigation reveals that the combination of mechanically softer nanoporous materials with ammonia refrigerants can achieve a high COP and a reduced system volume.